Crushed volcanic rock as soil remineralizer: a strategy to overcome the global fertilizer crisis (2022)
Transitioning the productive base to a more sustainable agriculture is one of the great challenges of our time. The current conflicts in Eastern Europe have had a major repercussion on the agricultural commodity market with restricted access and a massive cost increase for some fertilizers used in agriculture. This scenario has led to international concern about food shortages, whereby countries that depend on fertilizer imports need to find mechanisms and new technological paths to reduce their dependence on the international market. The use of crushed rock (soil remineralizers) associated with microorganisms is an important alternative in terms of cost reduction, lower impact on the environment and reduction of external dependence on agricultural inputs. The objective of this work was to evaluate the results of different types of inputs for soil fertilization (crushed rock – remineralizer, organic material and conventional – NPK), the production parameters of quinoa culture (Chenopodium quinoa) and this nutritional content of the crop. The experiment was carried out in a greenhouse and the data were subjected to analysis of variance, the Dunnett's test, complex contrasts, and multivariate analyses. The results showed significant increases in grain filling and quinoa yields, in soil fertility, and in the nutrient content of the aerial parts of plants treated with remineralizers. The treatments containing a mixture of remineralizers and organic compost were superior to those without these inputs, suggesting positive interaction among these sources. This approach may help toward adopting new technologies, especially with the current undersupply of soluble fertilizers. The use of local geological sources (crushed rock) has the capacity to reduce the dependence on imported fertilizers, thus helping to increase agri-food sovereignty in countries and adhering to the principles of agroecology at the local and global levels. © 2022, International Association for Mathematical Geosciences.